Integrasi Metode Everyone Is A Teacher Here dan Video Scribe untuk Memahami Teks Nonfiksi secara Kritis - Kamila, Diva; Iska, Zikri Neni (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2023)
The purpose of this study was to determine and examine the effect of applying the Everyone Is A Teacher Here method to students' critical thinking skills in understanding video scribe-based nonfiction texts for class V SDN Sukabumi Selatan 06 Pagi Jakarta Barat. The data collection technique uses a question instrument in the form of a descriptionconsisting of 10 valid and reliable questions. Data analysis techniques for the normality test used the Kolmogorov-Smirnov technique, for the homogeneity test used the Levene test with testing criteria based on mean, and for the t-test for hypothesis testing. In the experimental class, the average pretest score was 53.37 and the posttest average score was 72.57. Meanwhile, in the control class, the average pretest score was 48.95 and the posttest average score was 54.11. Based on the results of hypothesis testing with tcount 6.300 and ttable 1.67, it can be concluded that Ha is accepted or there is an effect of applying the Everyone Is A Teacher Here method to students' critical thinking skills in understanding nonfiction text based on video scribe class V SDN Sukabumi Selatan 06 Pagi Jakarta Barat